Neurocognitive Principles as the Basis for an Intuitive Design - Meneses, Eska Elena Solano (2021)
This work seeks to analyze the implications of neurocognitive sciences in design. Recent studies have allowed the reconceptualization of design from a semiotic approach. Scientists John O'Keefe, Edvard Moser, and May-Britt Moser have discovered the existence of cells in the brain whose system allows people to orient themselves, creating a mental map of physical space. Hence, the concept of Wayfinding is introduced, which is referred to as a way in which people can mentally plan to navigate from place to place or use objects, not as a simile of a visual-mental map, but as a process that it involves symbolic components and determining past experiences. Wayfinding demands different types of memory: episodic and usual (rigid) memories, their response from design is called Wayshowing, that is, the application of this knowledge to design. In this regard, the methodological proposal of Carlos Quiroga is taken, who, to make a diagnosis of the formal and symbolic compatibility of objects with the cognitive and interpretive capacity of the users, develops the concepts of Affordances and Conceptual Models applying them in the evaluation of objects in order to determine the compositional successes or failures.